The Patterns of Hate Speech in The Viewers' Comments Column on The Channel Youtube with The Topic of Puan Maharani In 2019 - Paramita, Tiara Pradnya; Subyantoro, Subyantoro; Pristiwati, Rahayu (Universitas Negeri Semarang, 2022)
Social media in its use nowadays does not only just pack information, but also provides opportunities to produce information and disseminate information. Furthermore, social media users have the right to choose, determine, and create informative messages or points of view they want; social media may now be a part of human existence and has been consumed massively including Youtube which is one of the most popular social media platforms. However, it cannot be denied that the function of social media can be likened to a double-edged sword; on the one hand it can be used for big activities, but on the other hand it can be used for bad things and is detrimental to society. The problem in this research was